Quantum‐Dot Fluorescence Lifetime Engineering with DNA Origami Constructs1. Issue 4 (23rd December 2012) - Ko, Seung Hyeon; Du, Kan; Liddle, J. Alexander
<x xml:space="preserve">Abstract</x> Single‐molecule GPS: The average photon count rate and lifetime of a quantum dot (Qdot) have been controlled by varying the geometrical configuration of Qdot–gold nanoparticle (AuNP) conjugates on DNA origami. With a 3D real‐time single‐molecule tracking system, which allows the DNA templates to be kept in their native state in solution, the influence of AuNPs on the Qdot lifetime is determined (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>